Using a web-based multilingual platform to support elementary refugee students in mathematics - Le Pichon, Emmanuelle; Cummins, Jim; Vorstman, Jacob (Journal of multilingual and multicultural development, 2024)
This exploratory study reports on the implementation of a novel web-based multilingual learning platform. This tool allows content to be delivered in different languages simultaneously, including languages of the students. In addition, it creates access to content knowledge aligned to the local curriculum, and in doing so, responds to an emerging need of both teachers and learners, in particular in light of an increasing linguistically and culturally diverse context. Our pilot research aimed to examine implementation elements and the perceived potential impact of the platform in mathematics. We conducted our study in an elementary school in the region of Toronto, Canada, attended by a significant number of students with a refugee background. A language biographical approach allowed us to highlight the role of the multilingual access to content knowledge, particularly on learning autonomy. Our results suggest that the use of this multilingual web-based platform may stimulate the learning autonomy of students and a positive attitude towards maths. In addition, our results suggest that additional strategies may be needed to improve the teachers' ability to implement digital as well as language friendly strategies in their classrooms.